Formation of Virtual Mothers' Group Communication in the Management of Chickenpox: An Analysis Based on George Homans' Group Formation Theory - Rafika Hani Hani; Leila Mona Ganiem (Indonesian Journal Publisher, 2026)
Chickenpox epidemic encourages the formation of the virtual group in school area as mediator in handling and changing the information. This research analyzes the construction process of virtual community